Perishing Heathens : Stories of Protestant Missionaries and Christian Indians in Antebellum America - Rubin, Julius H. (Book collections on Project MUSE., 2017)
"Perishing Heathens examines the missionary men and women who between 1800 and 1830 responded to the call to save Native peoples in missions, including the Osages in the Arkansas Territory; Cherokees in Tennessee and Georgia; and Ojibwe peoples in the Michigan Territory."--Provided by publisher